Association of Childhood IgA Vasculitis With Allergic Rhinitis and Chronic Rhinosinusitis - Weilin Xiong; Qingjun Zhu; Xiaolei Hu; Yehong Yuan; Yongwang Zhao; Xiaoping Jing; Qingyin Guo (Kidney International Reports)
Introduction: Immunoglobulin A vasculitis (IgAV) is related to chronic inflammation; however, little is known about the associations between IgAV and allergic rhinitis (AR) or chronic rhinosinusitis (CRS). We evaluated the relationships among IgAV, AR, and CRS in children. Methods: The clinical data of children with IgAV who were hospitalized from January to December 2019 were analyzed retrospectively. Four groups were created, the simple AR, simple CRS, AR + CRS, and non-AR or non-CRS groups, to explore the relationships among IgAV, AR, and CRS. Results: We included 504 children with IgAV; and 357 (70.8%) were combined with AR or CRS, including 51 with simple AR, 70 with simple CRS, and 236 with AR + CRS. The incidences of renal involvement and recurrent rash were significantly higher in the simple AR group than in the non-AR or non-CRS group (P < 0.001). The incidences of renal involvement and recurrent rash were significantly higher in the AR + CRS group than in the non-AR or non-CRS group (P < 0.001). The incidences of renal involvement between the simple CRS group and non-AR or non-CRS group did not differ significantly, but that of recurrent rash was significantly higher than that in the other groups (P < 0.001). Age, abdominal pain, recurrent rash, simple AR, and AR combined with CRS were risk factors for renal involvement (all odds ratio [OR] > 1, P < 0.05). Conclusion: Chronic rhinitis may be related to the pathogenesis of IgAV, and AR or CRS may be the triggering factors of IgAV. AR may be a risk factor for renal involvement and recurrent rash in patients with IgAV.